Miconia teotepecensis (Melastomataceae), una nueva especie de la Sierra Madre del sur de Guerrero y Oaxaca, México - de Santiago Gómez, Jesús Ricardo (Instituto de Ecología, A.C., 2000)
Miconia teotepecensis sp. nov. of the Sierra Madre del Sur in the states of Guerrero and Oaxaca is described and illustrated. Its placement within section Amblyarrhena and its relationships to other species are discussed.